Bahasa Indonesia-English Code-Mixing in Writing Business Emails: Understanding the Communicative Purpose - Andre, Robby (Bina Nusantara University, 2018)
The study had two objectives, those were to investigate the use of code-mixing in the business emails which could be categorized as asynchronous computer-mediated communication, and to calculate the most prevalent occurrences of codemixing in the business emails. The data were gathered from the business emails of Corporate Sales Officer in The British Institute Surabaya and its corporate clients from January to June 2017. Code-mixing typology acted as the primary tool in identifying and classifying the code-mixing in the data. The analysis of data yielded a total of 209 code-mixing occurrences. From the result, it can be seen that code-mixing insertion is ranked as the most prevalent occurrences of code-mixing with a total of 115 occurrences (55,02%). It is followed by code-mixing congruent lexicalization with 78 occurrences (37,32%),and code-mixing alternation with 16 occurrences (7,66%). Furthermore, the result of the study shows that the occurrences of code-mixing categories in the business emails may have some communicative purposes, such as emphasizing the main idea of the utterances or referring to the specific lexical items which deal with the knowledge of certain fields.